Response assessment after stereotactic body radiation therapy for spine and non-spine bone metastases: results from a single institutional study - Dora Correia; Barbara Moullet; Jennifer Cullmann; Rafael Heiss; Ekin Ermiş; Daniel M. Aebersold; Hossein Hemmatazad (Radiation Oncology, 2022)
Abstract Background The use of stereotactic body radiation therapy (SBRT) for tumor and pain control in patients with bone metastases is increasing. We report response assessment after bone SBRT using radiological changes through time and clinical examination of patients. Methods We analyzed retrospectively oligo-metastatic/progressive patients with bony lesions treated with SBRT between 12/2008 and 10/2018, without in-field re-irradiation, in our institution. Radiological data were obtained from imaging modalities used for SBRT planning and follow-up purposes in picture archiving and communication system and assessed by two independent radiologists blind to the time of treatment. Several radiological changes were described. Radiographic response assessment was classified according to University of Texas MD Anderson Cancer Center criteria. Pain response and the neurological deficit were captured before and at least 6 months after SBRT. Results A total of 35 of the 74 reviewed patients were eligible, presenting 43 bone metastases, with 51.2% (n = 22) located in the vertebral column. Median age at the time of SBRT was 66 years (range 38–84) and 77.1% (n = 27) were male. Histology was mainly prostate (51.4%, n = 18) and breast cancer (14.3%, n = 5). Median total radiation dose delivered was 24 Gy (range 24–42), in three fractions (range 2–7), prescribed to 70–90% isodose-line. After a median follow-up of 1.8 years (range < 1–8.2) for survivors, complete or partial response, stable, and progressive disease occurred in 0%, 11.4% (n = 4), 68.6% (n = 24), and 20.0% (n = 7) of the patients, respectively. Twenty patients (57.1%) died during the follow-up time, all from disease progression, yet 70% (n = 14) from this population with local stable disease after SBRT. From patients who were symptomatic and available for follow-up, almost half (44.4%) reported pain reduction after SBRT. Conclusions Eighty percent of the patients showed local control after SBRT for bone metastases. Pain response was favorable. For more accurate response assessment, comparing current imaging modalities with advanced imaging techniques such as functional MRI and PET/CT, in a prospective and standardized way is warranted. Trial registration Retrospectively registered.